Environmental determinants of obesity: A multidimensional assessment based on H.L. Blum’s health model in Riau, Indonesia - Qayyum, Abdullah; Afandi, Dedi; Nofrizal, Nofrizal; Nazriati, Elda (Edelweiss Applied Science and Technology, 2026)
The prevalence of obesity continues to increase globally and nationally, with Indonesia reporting a rising prevalence of 21.8% in 2018 and an increase in the number of obesity-related visits in Riau Province. Based on the H.L. Blum health model, this study examined the environmental determinants of obesity among 200 adults aged 15–59 years old who attended Posbindu PTM (Pos Binaan Terpadu Penyakit Tidak Menular/Integrated Development Post of Non-Communicable Diseases) in the working area of the Langsat Community Health Center (Puskesmas) in Pekanbaru City, Riau Province. Four environmental domains were assessed: socioeconomic factors, food availability, physical environment, and psychosocial conditions. Data were analyzed using Bivariate Analysis: Cramer's V Correlation Test to determine its correlation with Body Mass Index (BMI), which served as the outcome measure. Significant correlations were identified between BMI and factors such as type of employment, instant noodle consumption, sedentary work patterns, perceived advertising influence, and perceived social barriers. These findings underscore the significant role of environmental exposures in influencing obesity risk. An environment-based management model, grounded in Blum's framework, is proposed to assist policymakers in developing targeted interventions aimed at preventing further increases in obesity prevalence.